Crafting Medical Education Differently: An Innovative Pedagogical Approach to Enhance Deep Learning in Obstetrics and Gynaecology - Chivaugn Gordon; Veronica Mitchell; Gregory Doyle (University of Johannesburg, 2023)
In this article we explore an innovative pedagogical approach initiated during the COVID-19 lockdown period to support student learning in Obstetrics and Gynaecology in the Faculty of Health Sciences at the University of Cape Town. Student isolation and the lack of exposure to clinical cases during this period brought many challenges to the teaching platform. However, the global disruption enabled an ontological opening for imaginative and creative experimentation, an aspect of teaching rarely brought into medical training. We take up the unusual work of a clinician educator and others to describe the process of developing novel video recordings for undergraduate medical students. These videos, used as pedagogical tools, enabled new ways of engaging with core curricular needs in this discipline: for the teacher, new ways of producing teaching materials, and for the students, new ways of learning medical content. The videos drew on a range of creative modes including drawing and acting, to augment student learning. As authors, we suggest that the collision of the clinical content and the performative delivery in the videos fostered deep learning and made the curricular material alive and engaging. The existence of the videos enables a sustainable blended learning approach moving forward. The uploading of the videos as Open Educational Resources onto a YouTube channel and a public website now also contribute to teaching resources extending beyond institutional boundaries.